Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) terhadap Kemampuan Pemecahan Masalah Ditinjau dari Kemandirian Belajar - Rahmawati, Aulia; Meilasari, Venty (Eksponen, 2024)
The point of this exploration is to see if there is an impact of the Context oriented Educating and Learning (CTL) learning model on understudies' critical thinking skills in level sided space building material for class VIII SMP IT Insan Robbani, to figure out which critical abilities to think are better. between high, medium and low learning autonomy in class VIII understudies at SMP IT Insan Robbani, and to see if there is a collaboration between the learning model and learning freedom on the critical abilities to think of class VIII understudies at SMP IT Insan Robbani. Using a statistical group comparison research design, this study is experimental. A posttest, or final ability test, is used in the statistical group comparison research design. The populace in this review were all understudies of class VIII SMP IT Insan Robbani. The cluster random sampling method was used for the sampling. Two-way ANOVA was used to analyze the data. The following conclusions can be drawn from the data analysis: 1) The CTL learning model has an effect on one's ability to solve problems. 2) Understudies with high learning autonomy have a similar critical thinking skills as understudies with moderate mastering freedom, understudies with high learning autonomy have preferable critical abilities to think over understudies with low learning freedom, and understudies with moderate learning autonomy have preferred critical abilities to think better over understudies with low learning freedom. 3) The CTL learning model and independent learning on problem-solving skills do not interact.